Explosion Pressure and Minimum Explosible Concentration Properties of Metal Sulfide Ore Dust Clouds - Yun-zhang Rao; Chang-shun Tian; Wei Xu; Chun-yu Xiao; Bo-yun Yuan; Yao Yu (Journal of Chemistry)
The explosion pressure and minimum explosible concentration (MEC) properties of metal sulfide ore dust clouds are valuable for the prevention and control of metal sulfide ore dust explosions. In this study, a 20 L explosion sphere vessel was used to investigate the effect of sulfur content, particle size, and concentration on the explosion pressure and minimum explosible concentration of metal sulfide ore dust clouds. Four samples with different sulfur contents were selected (30%–40%, 20%–30%, 10%–20%, and 0%–10%). Before and after the explosion, samples were tested by X-ray diffraction. The results indicate that the metal sulfide ore dust is explosive dust with St1 grade explosion pressure. With an increase in concentration, the maximum explosion pressure increased at first and then decreased. With an increase in sulfide content, the explosion pressure of metal sulfide ore dust increased, while the minimum explosible concentration decreased. As particle size decreased, the MEC also decreased. The sulfur content, particle size, and concentration of metal sulfide ore dust were the main factors affecting the explosion hazard.